Targeting TL1A/DR3 Signaling Offers a Therapeutic Advantage to Neutralizing IL13/IL4Rα in Muco-Secretory Fibrotic Disorders - Steele, Hope; Sachen, Kacey; McKnight, Andrew J.; Soloff, Rachel; Herro, Rana (Frontiers in Immunology, 2021)
Mucus secretion is an important feature of asthma that highly correlates with morbidity. Current therapies, including administration of mucolytics and anti-inflammatory drugs, show limited effectiveness and durability, underscoring the need for novel effective and longer lasting therapeutic approaches. Here we show that mucus production in the lungs is regulated by the TNF superfamily member 15 (TL1A) acting through the mucus–inducing cytokine IL-13. TL1A induces IL13 expression by innate lymphoid cells leading to mucus production, in addition to promoting airway inflammation and fibrosis. Reciprocally, neutralization of IL13 signaling through its receptor (IL4Rα), completely reverses TL1A-induced mucus secretion, while maintaining airway inflammation and fibrosis. Importance of TL1A is further demonstrated using a preclinical asthma model induced by chronic house dust mite exposure where TL1A neutralization by genetic deletion or antagonistic blockade of its receptor DR3 protected against mucus production and fibrosis. Thus, TL1A presents a promising therapeutic target that out benefits IL13 in reversing mucus production, airway inflammation and fibrosis, cardinal features of severe asthma in humans.